Cognitive upgrading and its impact on organizational development study consensus sample of Iraqi Tourism Authority (The Peerian Journal, 2025)
The goal of the current study to know the strength of the relationship between research variables as an independent variable and organizational development as a variable in the Iraqi Tourism Authority and to reach a number of recommendations that promote the organizational development of the Authority and from the importance of the theme The study and its importance to organized and private organization, including individuals and sample society, have a significant impact on their level of work. The study applied the analytical descriptive approach by analyzing a sample of sample of the sample authorities in the course of the tourism (53) Sample distributed on (Director General, Assistant General Manager, Head of Division), which was comprehensively distributed, and received the researcher (43) questionnaire, and when unloading (10) questionnaires are not valid for analysis Statistical sample (43) with relying on statistical methods (honesty, stability, coefficient and (SPSS.V.SMART) Liaison coefficient and standard deviation) In order to identify the assessments of the study, it is through the side Practical has been reached a total of conclusions and recommendations have been the most important conclusion that the Tourism Authority has a good level of application of modern technologies, but there is a weakness in some potential and technical infrastructure that reflects gaps in the application, It refers to the lack of clarity of some strategies or varying awareness among employees. A recommendation is that the Tourism Authority must build programs to develop rapid thinking and provide a database and information, through the establishment of learning societies, in order to improve decision-making and raise the level of performance and production and promote organizational development of the Authority.